2017
DOI: 10.1097/pas.0000000000000807
|View full text |Cite
|
Sign up to set email alerts
|

GIST Manifesting as a Retroperitoneal Tumor

Abstract: Most gastrointestinal stromal tumors (GISTs) occur in the tubular gastrointestinal tract, but some present apparently outside the GI-tract. In this study, we analyzed 112 GISTs located in the retroperitoneum. These tumors occurred in 55 women and 57 men with a median age of 65 years (range: 21-89 years). Based on clinically or histologically detected connections to GI-tract, 15 tumors were considered likely of gastric, 9 duodenal, and 13 of small intestinal origin. The remaining cases were categorized by locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 39 publications
(24 reference statements)
0
21
0
Order By: Relevance
“… 25 Likewise, immunohistochemistry is essential for confirming the diagnosis of eGISTs. Findings from a retrospective analysis of a single institution 12 showed that 95% (106/112 cases), 62% (53/86 cases), and 93% (81/87 cases) of the eGIST patients were stained positive on IHC for CD117, CD34 and DOG-1, respectively. In a study, 26 the authors found that 92.2% (47/51 cases), 80.6% (25/31 cases), and 100% (13/13 cases) of the patients had positive staining with CD117, CD34 and DOG-1, respectively, on IHC from multi-institutional data collected in South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 25 Likewise, immunohistochemistry is essential for confirming the diagnosis of eGISTs. Findings from a retrospective analysis of a single institution 12 showed that 95% (106/112 cases), 62% (53/86 cases), and 93% (81/87 cases) of the eGIST patients were stained positive on IHC for CD117, CD34 and DOG-1, respectively. In a study, 26 the authors found that 92.2% (47/51 cases), 80.6% (25/31 cases), and 100% (13/13 cases) of the patients had positive staining with CD117, CD34 and DOG-1, respectively, on IHC from multi-institutional data collected in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the similarities in IHC and genetic testing between eGISTs and GISTs, the prognoses of eGISTs are less favorable compared to GISTs as the former tends to have higher proliferative mitotic indices (GISTs vs eGISTs, median range, 4–8/50 HPF 36 38 vs 10–15/50 HPF 12 , 39 , 40 ), larger tumor size (GISTs vs eGISTs, median range, 4–7 cm 38 , 41 , 42 vs 7.5–15 cm 12 , 14 , 39 , 40 , 43 ) and greater risk to recurrence or distant metastasis. 14 , 44 Similarly, our findings showed that the median tumor size (13 cm, range, 0.4–29 cm) and mitotic value (13 HPF, range, 0–50 HPF) were in accordance with that of reported literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29-33 E-GISTs generally share canonical morphologic, immunohistochemical, and molecular features of conventional GISTs, and E-GISTs primarily arising in the mesentery or retroperitoneum seem to follow a more aggressive clinical course 31, 33 , compared to cases arising in the omentum. 30 Some E-GISTs arise in the tubular GI tract but have become substantially detached from the gastric or intestinal primary site, which can therefore be clinically occult.…”
Section: Extragastrointestinal Gists and Gists Arising At Visceral Lomentioning
confidence: 99%
“…Origin from developmental abnormalities (such as enteric duplication) has also been proposed. 33 GISTs arising primarily in visceral organs are exceedingly rare, and have not been systematically studied. 34, 35 GISTs manifesting primarily in visceral organs such as the liver or spleen most likely represent distant metastases from an occult GI tract primary GIST.…”
Section: Extragastrointestinal Gists and Gists Arising At Visceral Lomentioning
confidence: 99%